TATA KRAMA BERBICARA PESERTA DIDIK DI LINGKUNGAN SEKOLAH SEBAGAI BENTUK PENERAPAN ELEMEN BERAKHLAK MULIA - Hanum, Latifah; Tomasouw, Jolanda; Marantika, Juliaans E. R (Jurusan Pend. MIPA FKIP Universitas Pattimura, 2024)
Manners are regular appearance or behaviour in a good manner. Manners involve several aspects such as speaking, body movements, social relationships and others. Good manners must be applied in the living environment by anyone, including students. Students must be able to implement good manners. Examples include the application of good speaking etiquette between fellow students, students and educators at school, students and their parents at home and students and other people in the community. Implementing good speaking etiquette is an example of implementing elements of noble character in Pancasila Profile Education (PPP). One example of implementing good speaking etiquette among students at SMPN 4 Ambon is saying something wrong when meeting educators in the school environment. SMPN 4 Ambon is a school that has implemented anti-bullying and violence in its school environment